Side effects of green technologies: the potential environmental costs of Lithium mining on high elevation Andean wetlands in the context of climate change - Izquierdo, Andrea Elisa (2015)
Lithium-based batteries are the key component of booming green technologies, including hybrid electric, plug-in hybrid electric and battery electric vehicles. Nearly 80% of the global lithium resources are located in the subtropical “Puna” highlands of Argentina, Bolivia and Chile. In these arid ecosystems, most biodiversity is related to wetlands: this highly valuable biodiversity includes the emblematic native camelids, flamingos, and a rich variety of endemic plants, and other animals. Climatic trends during the past decades, and future climate models suggest persistent drying tendencies. As other mining operations, lithium exploitations of salty flats require relatively large amounts of water. We discuss the research questions and priorities to preserve these valuable ecosystems in the context of growing potential conflicts for the use of water.